Diverse mechanisms of metaeffector activity in an intracellular bacterial pathogen, Legionella pneumophila. Issue 12 (16th December 2016) - Urbanus, Malene L; Quaile, Andrew T; Stogios, Peter J; Morar, Mariya; Rao, Chitong; Di Leo, Rosa; Evdokimova, Elena; Lam, Mandy; Oatway, Christina; Cuff, Marianne E; Osipiuk, Jerzy; Michalska, Karolina; et al.
Abstract: Pathogens deliver complex arsenals of translocated effector proteins to host cells during infection, but the extent to which these proteins are regulated once inside the eukaryotic cell remains poorly defined. Among all bacterial pathogens, Legionella pneumophila maintains the largest known set of translocated substrates, delivering over 300 proteins to the host cell via its Type IVB, Icm/Dot translocation system. Backed by a few notable examples of effector–effector regulation in L. pneumophila, we sought to define the extent of this phenomenon through a systematic analysis of effector–effector functional interaction. We used Saccharomyces cerevisiae, an established proxy for the eukaryotic host, to query > 108, 000 pairwise genetic interactions between two compatible expression libraries of 330 L. pneumophila‐ translocated substrates. While capturing all known examples of effector–effector suppression, we identify fourteen novel translocated substrates that suppress the activity of other bacterial effectors and one pair with synergistic activities. In at least nine instances, this regulation is direct—a hallmark of an emerging class of proteins called metaeffectors, or "effectors of effectors". Through detailed structural and functional analysis, we show that metaeffector activity derives from a diverse range of mechanisms, shapes evolution, and can be used to reveal important aspects of each cognate effector's function. Metaeffectors, along with other, indirect, forms of effector–effector modulation, may be a common feature of many intracellular pathogens—with unrealized potential to inform our understanding of how pathogens regulate their interactions with the host cell. Synopsis: Pairwise genetic interaction mapping between Legionella pneumophila effectors, followed by functional and structural analyses, reveals diverse mechanisms of effector–effector modulation. Over 220 L. pneumophila effectors cause a growth defect when ectopically expressed in S. cerevisiae, likely reflective of targeting fundamental eukaryotic biology. Pairwise genetic‐interaction mapping between effectors uncovers 14 instances where one or more effectors rescue another's growth defect and one in which two effectors specifically synergize to restrict yeast growth. Protein–protein interactions indicate direct effector‐effector regulation (metaeffector activity) for nine pairs. Structure‐function analyses, including the first ever effector–metaeffector complex crystal structure, reveal a diversity of mechanisms supporting effector–effector modulation. Abstract : Pairwise genetic interaction mapping between Legionella pneumophila effectors, followed by functional and structural analyses, reveals diverse mechanisms of effector–effector modulation.